BARRIER OF REFERRAL–BACK IN SECONDARY HEALTH FACILITIES: PROVIDER AND PATIENT PERSPECTIVES - Larasati, Putu Cindy Elisya Intan; Ulandari, Luh Putu Sinthya (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: The referral-back program (RBP) is a program for chronic outpatient patients at hospitals to return to access services at first-level health facilities (Primary Healthcare Centers/ PHC) once their condition has been declared stable by the doctor. However, data indicate that many hospitals and clinics in Denpasar City have not met the RBP target. Aims: This study aimed to explore the implementation of RBP and the challenges faced by providers and patients. Methods: Conducted in March 2023, this study used a qualitative approach with in-depth interviews. The sample was determined purposively, consisting of 13 informants. The data were analyzed using the thematic method. Results: From the provider's perspective, issues included low commitment of medical staff, lack of coordination between the hospital and PHC, limited supply of RBP drugs at the PHC, absence of Standard Operating Procedures (SOPs), and ignorance of notifications regarding potential RBP patients. Moreover, from the patient's perspective, challenges included low patient knowledge about RBP, proximity of the patient's house to the hospital so that patients tend to visit the hospital, difficulty in obtaining RBP drugs at PHC, and ineffective procedures. Conclusion: To overcome these obstacles, coordination, and improvement of RBP are needed through the preparation of SOPs and determination of RBP patient criteria. Keywords: barrier, implementation, referral-back program